2019
DOI: 10.1242/jeb.203687
|View full text |Cite
|
Sign up to set email alerts
|

Early feeding of rainbow trout (Oncorhynchus mykiss) with methionine deficient diet over a two-week period: consequences for liver mitochondria in juveniles

Abstract: Methionine is a key factor in modulating the cellular availability of the main biological methyl donor S-adenosylmethionine (SAM), which is required for all biological methylation reactions including DNA and histone methylation. As such, it represents a potential critical factor in nutritional programming. Here, we investigated whether early methionine restriction at first feeding could have long-term programmed metabolic consequences in rainbow trout. For this purpose, trout fry were fed with either a control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…In agreement to present results, co-feeding regimes from mouth opening have been reported to enhance growth and survival of Senegalese sole (Cañavate & Fernández-Díaz, 1999;Engrola, Figueira, et al, 2009) and loach (Wang et al, 2009) after weaning. Present results also corroborate the scientific findings that indicate that changes in environment or nutrition during the critical developmental stages may influence the subsequent postlarvae and juvenile performance (Koedijk et al, 2010;López-et al, 2003;Perera & Yúfera, 2016;Séité et al, 2019;Vagner et al, 2007).…”
Section: Ta B L Esupporting
confidence: 90%
“…In agreement to present results, co-feeding regimes from mouth opening have been reported to enhance growth and survival of Senegalese sole (Cañavate & Fernández-Díaz, 1999;Engrola, Figueira, et al, 2009) and loach (Wang et al, 2009) after weaning. Present results also corroborate the scientific findings that indicate that changes in environment or nutrition during the critical developmental stages may influence the subsequent postlarvae and juvenile performance (Koedijk et al, 2010;López-et al, 2003;Perera & Yúfera, 2016;Séité et al, 2019;Vagner et al, 2007).…”
Section: Ta B L Esupporting
confidence: 90%
“…PARPs are involved in chromatin regulation, transcription, RNA biology, and DNA repair. PARP, as a prominent marker of apoptosis was upregulated in rainbow trout, revealing apoptosis induction under endoplasmic reticulum stress ( Séité et al., 2019 ). PARP acts on both host and viral proteins through binding to deltex E3 ubiquitin ligase 3L (DTX3L) to mediate efficient immune responses to pathogens ( Gupte et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In teleost fish, although only few studies have been conducted, the concept of programming has also been demonstrated in different species [15], and a particular focus has been given to aquaculture species [16]. Several studies have focused on different stimuli given during the early feeding phase and their long term consequences [17][18][19][20][21]. The consequences of stimuli applied earlier in development i.e., during gametogenesis, have also been tested.…”
Section: Introductionmentioning
confidence: 99%